Investigation of Polarization Preservation in Water Channel by Using Mueller Matrix Based on Single Photon Detection - Ghada Qusai Ramzi; Ahmed Ismael Khaleel (Iraqi Journal of Laser, 2024)
Polarization encoding in quantum key distribution systems is widely used for distributing secret keys between a sender and a receiver. As the polarization-encoded photons pass through the quantum channel, their polarization states might be changed. A prior verification of the channel characteristic is required in order to investigate the effect of the channel on the polarization of the photons passing through it. In this work, an experimental investigation of polarization preservation of a pure water channel is presented. The investigation relies on the verification of the Mueller matrix in order to check the polarization preservation of the channel. The measurements were carried out using a single photon detection module. The results showed that the polarization of the optical pulses is preserved when passing through the pure water channel and it can be used as a quantum channel in the quantum key distribution systems.